Penggunaan Media YouTube dalam Meningkatkan Keterampilan Mendengar Bahasa Arab Kelas X MA Al-Ikhlas Labunti Raha Sulawesi Tenggara - Mujahid Abdul Jabbar; Fitrayani Kahar; Wahyudin Wahyudin (Education and Learning Journal, 2022)
This research demonstrates the use of YouTube media in improving Arabic listening skills at MA AL-Ikhlas Labunti Raha School, Southeast Sulawesi. The purpose of this study was to determine the use of YouTube media in improving Arabic listening skills in MA AL-Ikhlas Labunti Raha, Southeast Sulawesi, dan to facilitate students' learning of Arabic through educational videos on YouTube because it can be accessed anytime anywhere. This Type Of Research is qualitative research that seeks to describe and explore data naturally and comprehensively, in addition to providing an in-depth explanation or evaluation and following developments based on the problems posed. The data collection techniques used are observation dan residence interviews. The data analysis technique used in this study is to collect three types of data, which are qualitative data in the form of observational data, interviews, and documentation. The data will be analyzed qualitatively, which means that all the data will be explained in depth based on the research problem. The results of this study indicate that the YouTube method in Arabic subjects can improve the listening skills of class 10 students at MA AL-Ikhlas Labunti Raha, Southeast Sulawesi. Qualitative evidence of documentation from observations, interviews, and documentation of class 10 MA students at Fidelity Labunti Raha, Southeast Sulawesi.